Revealing the Missing Link : Private Sector Supply-Side Readiness for Primary Maternal Health Services in Indonesia - Yap, Wei Aun; Pambudi, Eko Setyo; Marzoeki, Puti; Salcedo Cain, Jewelwayne; Tandon, Ajay (World Bank, Washington, DC, 2017)
Every six hours, the death of a woman from the complications of pregnancy serves as the most vexing reminder of Indonesia’s challenges with maternal health (MH). This is incommensurate with Indonesia’s strong economic development and stature compared with regional peers, especially as MH is a marker of overall health system performance and affects economic opportunities especially for the poor. The maternal mortality ratio (MMR) is high and progress on improving MH outcomes has been slow, such that the MH Millennium Development Goal (MDG) has already been missed. This policy paper analyzes new data on the ‘missing link’ of primary MH service provision, i.e., private providers, which is critical given that 54 percent of all deliveries in Indonesia occurred in the private sector, compared with 22 percent in the public sector, although overall rates of institutional deliveries remain below target. Key findings from the analysis elucidate the potential value of the private sector in expanding access to MH services covered by the financial purchasing and strategic purchasing umbrella of JKN, the effectiveness of these private MH services, and patient satisfaction. The remainder of the policy paper is structured as follows: The next section provides some background on Indonesia, including general health-related outcomes and an overview of the country’s health system and financing. Section III focuses on MH outcomes and context, including comparisons with global peers, and provides an overview of provision, utilization, and financing of MH services in the country, underscoring the importance of private providers. Section IV summarizes the distributional context and service readiness of private MH providers across the 64 high-priority districts, including a comparison with public providers for context. Section V concludes with a summary of key findings and their policy implications.